Exploring the obesity concerns of British Pakistani women living in deprived inner‐city areas: A qualitative study - Halima Iqbal; Jane West; Rosemary R. C. McEachan; Melanie Haith‐Cooper (Wiley, 2022)
Abstract Introduction British South Asians have a higher prevalence of overweight and obesity than the wider population. Bradford (UK), with its high Pakistani presence and levels of economic deprivation, has exceptionally high instances, especially in deprived areas where many Pakistanis reside. British Pakistani women in Bradford are more likely to be overweight and obese. There is uncertainty on how these women can be aided to manage their weight. Therefore, the objective of this study was to explore the obesity concerns of Pakistani women living in deprived inner‐city areas of Bradford. Methods Three focus groups interviews were carried out with 23 Pakistani women living in deprived areas of Bradford. Data were analysed thematically. Results This exploratory study identified a wide range of concerns that women had around managing their weight. Participants disclosed distrust in information given around medication, conflicting dietary information and reported low levels of trust in women‐only organized physical activities. Cultural barriers were identified, which included the gender role of the woman, the lack of culturally appropriate dietary advice, cultural misunderstandings of what constitutes a healthy diet and healthy weight, the lack of culturally suitable exercise facilities and conforming to family and community expectations. Other concerns were language barriers around a lack of understanding, the inability to read Urdu and reliance on others to translate information. Conclusion These findings have implications for researchers, local authorities, policy makers and others with an interest in reducing the rates of obesity in this population. Recommendations include training health practitioners to be culturally aware of the diet and eating practices of this community, exploring different ways to support socially isolated women to be more physically active at home, addressing physical activity and diet misconceptions and designing obesity management information materials appropriate for a range of literacy levels. Patient or Public Contribution Public contributors were involved in the development of the interview guide and design of the research. A pilot focus group with participants not included in the present paper was used to help test and refine the focus group questions. Interview transcripts were member checked by participants, and participants assisted with data analysis.